The astrocytic response to the dopaminergic denervation of the striatum. Issue 1 (18th June 2016) - Morales, Ingrid; Sanchez, Alberto; Rodriguez‐Sabate, Clara; Rodriguez, Manuel
Abstract : The dopaminergic denervation of the striatum induced a severe astrogliosis with a specific profile which included some (e.g. up‐regulation of GFAP, GS, S100β, NDRG2, vimentin) but not all (e.g. astrocytic proliferation or differentiation from NG2 cells, astrocytic scars, microgliosis) the characteristics observed after the non‐selective striatal lesions. This response may help to understand the role of striatal astrocytes during the dopaminergic denervation which characterizes the first stages of PD. Cover Image for this issue: doi:10.1111/jnc.13336 . Abstract: Increasing evidence suggests that the dopaminergic degeneration which characterizes Parkinson's disease starts in the striatal dopamine terminals and progresses retrogradely to the body of dopamine cells in the substantia nigra. The role of striatal astrocytes in the striatal initiation of the dopaminergic degeneration is little known. This work was aimed at studying the astrocytic response to the dopaminergic denervation of the striatum. The injection of 6‐hydroxydopamine (25 μg) in the lateral ventricle of adult Sprague–Dawley rats induced a fast (4 h) and selective (unaccompanied by unspecific lesions of striatal tissue or microgliosis) degeneration of the dopaminergic innervation of the striatum which was followed by a selective astrocytosis unaccompanied by microgliosis. This astrocytosis was severe and had a specific profile which included some (e.g. up‐regulation of glial fibrillary acidic protein, GS, S100β, NDRG2, vimentin) but not all (e.g. astrocytic proliferation or differentiation from NG2 cells, astrocytic scars, microgliosis) the characteristics observed after the non‐selective lesion of the striatum. This astrocytosis is similar to those observed in the parkinsonian striatum and, because it is was unaccompanied by changes in other striatal cells (e.g. by microgliosis), it may be suitable to study the role of striatal astrocytes during the dopaminergic denervation which characterizes the first stages of Parkinson's disease. The dopaminergic denervation of the striatum induced a severe astrogliosis with a specific profile which included some (e.g. up‐regulation of GFAP, GS, S100β, NDRG2, vimentin) but not all (e.g. astrocytic proliferation or differentiation from NG2 cells, astrocytic scars, microgliosis) the characteristics observed after the non‐selective striatal lesions. This response may help to understand the role of striatal astrocytes during the dopaminergic denervation which characterizes the first stages of PD. Cover Image for this issue: doi:10.1111/jnc.13336 .